Pengaruh Media Pembelajaran Berbasis Game Puzzle Terhadap Motivasi Belajar Siswa Kelas IV Pada Mata Pelajaran Bahasa Indonesia Di SDN 22 Kendari - Satriadin Satriadin; Erwin Eka Saputra; Ahmad Ahmad (Journal of Humanities, Social Sciences, and Education, 2025)
This study used a quantitative approach with a Quasi-Experimental Design. The research design used a Nonequivalent Control Group Design. The population and sample were 53 fourth-grade students at SDN 22 Kendari. Data collection included observation, questionnaires, and documentation. Data were analyzed using descriptive and inferential statistical analysis. Based on the results of the study, it can be concluded that puzzle game-based learning media has an effect on fourth-grade students' learning motivation in Indonesian language at SDN 22 Kendari. This was also determined by the t-test. The results of this study were: t = 1.248 with a Sig. (2-tailed) value of 0.219. To determine the distribution of the t-table, the value was calculated using df = 42, with a significance level of 0.609. Since the calculated t value > t table (1.248 > 0.267) and the Sig. (2-tailed) 0.001 < 0.05, Ho is rejected, thus stating that there is a significant effect of the use of puzzle-based game learning media on the learning motivation of fourth-grade students in Indonesian language at SDN 22 Kendari, providing a significant positive effect.